CARM1 is an important determinant of ERα-dependent breast cancer cell differentiation and proliferation in breast cancer cells - Al-Dhaheri, Mariam (2011)
Breast cancers expressing estrogen receptor α (ERα) are often more differentiated histologically than ERα-negative tumors, but the reasons for this difference are poorly understood. One possible explanation is that transcriptional co-factors associated with ERα determine the expression of genes which promote a more differentiated phenotype. In this study, we identify one such cofactor as coactivator associated arginine methyltransferase 1 (CARM1), a unique co-activator of ERα that can simultaneously block cell proliferation and induce differentiation through global regulation of ERα-regulated genes. CARM1 was evidenced as an ERα co-activator in cell-based assays, gene expression microarrays, and mouse xenograft models. In human breast tumors, CARM1 expression positively correlated with ERα levels in ER+ tumors but was inversely correlated with tumor grade. Our findings suggest that co-expression of CARM1 and ERα may provide a better biomarker of well-differentiated breast cancer. Further, our findings define an important functional role of this histone arginine methyltransferase in re-programming ERα-regulated cellular processes, implicating CARM1 as a putative epigenetic target in ER-positive breast cancers.